Biologia populacional e ecologia trófica de decápodes dulcícolas do rio Araguari, Minas Gerais - Barboza, Ana Claudia Garcia (2024)
Decapods are abundant and diverse, playing significant ecological roles in freshwater ecosystems. This study investigated aspects of the population biology and trophic ecology of freshwater decapods, focusing on the crab Dilocarcinus pagei and the shrimp Macrobrachium pantanalense in the Araguari River, southeastern Brazil. Chapter 1 analyzed the reproductive biology of D. pagei, including size, sex, demographic groups, and environmental factors such as rainfall and water level. Male crabs predominated in most months, with an increase in ovigerous females during periods of higher rainfall, suggesting that reproductive seasonality in this species is influenced by environmental factors. In Chapter 2, the natural diet of D. pagei was examined according to demographic groups and seasonal variations. Analyses of stomach contents revealed a predominantly plant-based diet, with small invertebrates and invasive mollusks, and juvenile females consuming more plant tissue during the rainy season. Chapter 3 used stable isotope analyses (δ¹³C and δ¹⁵N) to investigate trophic interactions and niche overlap between D. pagei and M. pantanalense. The results showed that D. pagei had a broader isotopic niche, indicating a greater diversity of resources, while M. pantanalense had higher δ¹⁵N values, indicating a higher trophic position. Low niche overlap suggests distinct feeding strategies, supporting the coexistence of these species in the same habitat. These findings provide insights into ecological interactions and contribute to the understanding of the adaptation and management of decapod crustaceans in impacted tropical ecosystems.